The Views of Mental Health Professionals Who Use Digital Methods to Support Care-Experienced Young People. Issue 2 (15th March 2023) - Cummings, Aimee
Abstract : The mental health of care experienced young people is a public health priority, with these individuals more at risk of experiencing poor mental health. While most mental health interventions have previously been delivered in-person, in the wake of the coronavirus pandemic many services were forced to change to a digital or blended format. While digital methods have been of great research interest, to date there has been scant research investigating the use of these methods with care experienced young people. The objective of this study was to explore the viewpoints of professionals who had experience of delivering digital mental health support to this group. A qualitative research design was employed, with ten semi-structured interviews conducted and analysed using a grounded theory approach. Themes relating to the move to online working, ensuring privacy and confidentiality online and accessibility of digital methods are discussed, as well as professionals' intended method of future service delivery. Professionals were cautious to remove all in-person work with care experienced young people but were optimistic that, by providing an option to work digitally, there was the potential to provide services to a whole new group of service users who had previously been unable to access help.